COVID-19: prevention and future initiative within nursing homes - Wrona, Marysia; Tobis, Sławomir; Wieczorowska-Tobis, Katarzyna; Neumann-Podczaska, Agnieszka (Journal of Medical Science, 2020)
The high COVID-19 mortality rate in nursing homes in the United States and internationally prompted a comprehensive mini literature review concerning the prevalence, preventative protocol, and proactive initiatives against the highly infectious COVID-19. PubMed articles published between January and June 2020 and data sourced from government ministries of health concerning COVID-19 in nursing homes were used for this review. The prevalence and mortality rate in seven countries were compared. The underlying theme of the articles reviewed addressed four focus areas for the prevention of infectious disease spread: diagnostics, protection of residents in nursing facilities, administration and staff protection, and legislative advocacy. Adaptations and solutions may reduce the current transmission of COVID-19 within nursing homes, as well as in the future.